Wireless body area networks for intra-spacesuit communications: modeling, measurements and wearable antennas - Taj-Eldin, Mohammed (Kansas State University, 2015)
Wireless body area networks (WBANs) are an important part of the developing internet of things (IOT). NASA currently uses space suits with wired sensors to collect limited biomedical data. Continuous monitoring and collecting more extensive body vital signs is important to assess astronaut health. This dissertation investigates wireless biomedical sensor systems that can be easily incorporated into future space suits to enable real time astronaut health monitoring. The focus of the work is on the radio-wave channel and associated antennas. We show that the space suit forms a unique propagation environment where the outer layers of the suit’s thermal micrometeoroid garment are largely radio opaque. This environment can be modeled as a coaxial one in which the body itself plays the role of the coax center conductor while the space suit shielding materials play the role of the outer shield. This model is then validated through simulations and experiments. Selecting the best frequency of operation is a complex mixture of requirements, including frequency allocations, attenuation in propagation, and antenna size. We investigate the propagation characteristics for various frequency bands from 315 MHz to 5.2 GHz. Signal attenuation is analyzed as a function of frequency for various communication pathways through 3D simulations and laboratory experiments. Small-scale radio channel results indicate that using lower frequency results in minimal path loss. On the other hand, measurements conducted on a full-scale model suggest that 433 MHz and 2400 MHz yield acceptable path loss values. Propagation between the left wrist and left ankle yielded the worst overall path loss, but signals were still above –100 dBm in raw measurements for a 0dBm transmission indicating that the intra-suit environment is conducive to wireless propagation. Our findings suggest that the UHF bands are best candidate bands since there is interplay between the body conductivity favoring lower frequencies, and the difficulty of coupling RF energy into and out of the channel using suitably sized antennas favoring higher frequencies. Finally, a new self-shielded folded bow-tie antenna is proposed that can be a promising choice for the general area of WBAN technologies as well as potential new space suit environments.
Keywords: Astronaut; Body area networks; EMU; Path loss; Performance; Radio channel; Space suit; Wearable antennaAntennas; Biomedical Engineering (0541); Electrical Engineering (0544); Electromagnetics (0607)